Usaha Pengoptimalan Efektivitas Proses produksi Percetakan Produk Pada Divisi Offset Di PT. Citra Sastra Grafika - Fatma, Nur Fadilah; Ponda, Henri; As’seghaf, Nurkholis (Journal Industrial Manufacturing, 2023)
The rapid development of the printing industry (printing) requires companies to continue to survive and develop. Companies that are able to survive and develop well can certainly increase the advantage of competition in the world of printing industry. Therefore, companies must have effective operating management in determining the number of workers and work balance seen from the performance factor of manpower and the efficiency of the production process so that it does not occur Waste of time and cost of production and operation activities can run well if the printing company has a good balance. The data obtained from observations is then grouped into several sub-groups and is investigated whether the average sub group is within the control limit of line balance or Better known as Line Balancing is a production strategy to balance time and workload in a number of interconnected processes in a production line so that there is no excessive congestion or capacity. Takt time time is the time needed by production in producing each product unit in order to meet customer demand. If the production time and production target have been determined, the measurement of work time is the activity of observing the work and recording the work time aims to obtain a reference value one time called the standard time to increase the company's production efficiency, especially in the production of books printing, it is necessary to have an effort to improve the production system and The balance of the production path using the linebalancing method, especially in this analysis, has the best method, namely the longest time method (Largest Candidate Rules Method) Keywords: Process, Raw Materials, Regional Operational Time Methods (Region Approach Method), Regional Operational Time Methods (Region Approach Method), Largest Candidate Rules Method